The Role of Organizational Citizenship Behavior in Mediating the Relationship between Servant Leadership and Job Satisfaction on the Performance of Civil Servants in Aceh Province, Indonesia - Harmen, Hamdi; Putra, Zainal; Rafiie, Said Achmad Kabiru; Rahmadani, Ika; Hidayat, Muhammad Rahmat; Rusdi, Rusdi; Muzammil, Abdul (Universitas Syiah Kuala, 2025)
Purpose This research purposes to explore the impact of servant leadership and job satisfaction on the performance of civil servants in the Indonesian language pegawai negeri sipil (PNS). Moreover, we also examine the role of organizational citizenship behaviour (OCB) as a mediator of the association with the servant leadership and the job satisfaction on the performance of civil servants.Design/Methodology We used simple random sampling techniques and selected 210 respondents. The data was examined by the partial least squares structural equation modelling (PLS-SEM) method with the help of software SmartPLS.Results The study results to show partially the servant leadership, the OCB and the job satisfaction significantly impact to the civil servant performance. Servant leadership significantly influences civil servant performance. In addition, OCB acts as a mediator in the relationship between servant leadership and job satisfaction on civil servant performance.Research limitations The results obtained should be interpreted with alert because they are confined to the specific geographical area along with the nature of the respondents selected.Implications The results reported in this study can guide the management to be able to increase the performance of civil servants via enhanced roles of servant leadership (SL), job satisfaction (JS) and organizational citizenship behavior (OCB).Novelty/Originality The study proves the role of OCB as complementary mediation, especially in the context of civil servants in Indonesia.